(untitled) (Research, Society and Development, 2022)
Considering the proposals for mathematical activities developed in the classes, we highlight the lack of relationship between these situations and problems experienced or close to the reality of the students, and having as an excellent auxiliary alternative for the classes, we aim to use Mathematical Modeling to make these mathematical contents closer to their reality, that is, it would make it possible to verify in the practice of these activities, through research, the use of Mathematical Models, which try to answer a certain social problem by answering it, thus making the student the main investigator of this process. Thus, through an exploratory research, we seek to analyze in the activities developed with the application of Mathematical Modeling and in the expectations of these authors, ways of analyzing the procedures that are adopted for the execution of this activity. In this context, we find the proposals suggested by Burak, which will guide the realization of a descriptive activity proposal. Therefore, we observe that it is an excellent alternative to demystify problems related to the teaching of mathematics.